Ways to design a digital educational environment for K-12 education - Natalia V. Morze; Viktoriia O. Kucherovska (Academy of Cognitive and Natural Sciences, 2021)
Most educational institutions strive to create favourable conditions for students which meet educational needs of each student. It leads to high demand in the digital educational environment of K-12 education institutions. The article is devoted to the description of the concept, components and ways of designing the digital educational environment of a K-12 education institution through the transformation of educational activities. The importance of developing an educational policy of an educational institution in the field of digital technology is described. Authors present the model and the ways of designing the digital educational environment of the K-12 education institution. The necessity of self-assessment of digital technologies usage in the educational process by all its participants is substantiated; the ways of application of the European tool SELFIE for carrying out such self-analysis are described. Based on the adaptation of all components of the tool SELFIE for Ukrainian education, the results of its usage at one of the secondary schools in Kyiv are presented.